SEGITIGA DIDAKTIS CERPEN MERAWAT PETI INGATAN KARYA PUTU OKA SUKANTA - Muhammad Rifqi Ainun Najib (PBSI, FKIP UNISSULA, Semarang, 2017)
This research used short story entitled â€œMerawat Peti Ingatanâ€by Putu Oka Sukanta as the object. The short story directed the readerâ€™s thinking to alwayshave critical thinking on everything and not easy to believe in a thing without any good reason underlying it. The approach used in this study is didactic approach or often called the value of education, while the type of research used is qualitative research. The purpose of this study to describe the projection of didactical sentence in the short story. This research began by reading and looking carefully the didactic elements contained in the short story. Then the data in the form of didactic elements are grouped by family, religion, and social didactic elements. From some of these processes it is found that there are didactic elements in religious, family, and social domains such as respect or modesty, humility, honesty and transparency, caring, gratitude, etc. Based on these studies it can be seen that social didactic elements are more prominent than religious and family didactic elements. It is caused by human social life which is more often done compared to other elementary.